Sealing glass and preparation method thereof

Through the combination of raw materials such as SiO2, Al2O3, Na2O, K2O, BaO and Co3O4, the problem of unstable performance of sealing glass is solved, the thermal expansion coefficient, chemical stability and softening temperature are improved, the sealing process is simplified and the scope of application is expanded. .

CN119191714AInactive Publication Date: 2024-12-27XIAN QINCHUANG CHAONENG TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411521536.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sealing glass has unstable performance, and the thermal expansion performance, chemical stability and softening temperature are not ideal, resulting in complex sealing process and small application range.

Method used

Using the combination of raw materials such as SiO2, Al2O3, Na2O, K2O, BaO and Co3O4, a sealed glass with a high thermal expansion coefficient, improved chemical stability and softening temperature is formed through a specific molar percentage ratio and preparation method, and the sealed glass with a high thermal expansion coefficient, improved chemical stability and softening temperature is formed, and the sealed glass with Co3O4 is passed through Co3O4. Add to optimize the optical properties and mechanical properties of glass.

Benefits of technology

The thermal expansion coefficient, chemical stability and softening temperature of the sealed glass are improved, the mechanical properties and corrosion resistance of the glass are enhanced, the softening point temperature is reduced, the sealing process is simplified, and the scope of application is expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191714A_ABST
    Figure CN119191714A_ABST
Patent Text Reader

Abstract

The invention provides sealing glass and a preparation method thereof, and relates to the technical field of sealing glass. The sealing glass is prepared from the following raw materials in percentage by mole: 35 percent to 60 percent of SiO2, 1 percent to 20 percent of Al2O3, 2 percent to 20 percent of Na2O, 2 percent to 20 percent of K2O, 0.5 percent to 25 percent of BaO and 0 percent to 15 percent of Co3O4. The sealing glass disclosed by the invention has high thermal expansion coefficient, glass softening temperature, chemical stability and identifiability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of sealing glass, and in particular to a sealing glass and a preparation method thereof. Background Art

[0002] As an inorganic adhesive, sealing glass is widely used in vacuum electronics, microelectronics, laser and infrared technology, energy, various industries and testing. However, the performance of existing sealing glass is not stable. The use of this kind of sealing glass leads to a more complicated sealing process, lower working stability and a smaller scope of application.

[0003] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0004] The present invention provides a sealing glass and a preparation method thereof, which can improve the thermal expansion coefficient, glass softening temperature, chemical stability and identifiability of the sealing glass.

[0005] According to one aspect of the present disclosure, a sealing glass is provided, wherein the sealing glass comprises the following raw materials in molar percentage:

[0006] SiO2: 35% to 60%, Al2O3: 1% to 20%, Na2O: 2% to 20%, K2O: 2% to 20%, BaO: 0.5% to 25%, Co3O4: 0% to 15%.

[0007] In an exemplary embodiment of the present disclosure, the raw materials of the sealing glass further include one or more of MgO and / or ZnO, wherein the molar percentage of the MgO is 0% to 10%, and the molar percentage of the ZnO is 0% to 15%.

[0008] In an exemplary embodiment of the present disclosure, the raw materials of the sealing glass also include one or more of CaO, P2O5 or ZrO2, wherein the molar percentage of CaO is 0% to 8%, the molar percentage of P2O5 is 0% to 8%, and the molar percentage of ZrO2 is 0% to 6%.

[0009] In an exemplary embodiment of the present disclosure, the sealing glass further includes Rb2O, and the molar percentage of Rb2O is 0% to 10%.

[0010] In an exemplary embodiment of the present disclosure, the raw material of the sealing glass further includes Bi2O3 or B2O3, wherein the molar percentage of the Bi2O3 is 0% to 10%, and the molar percentage of the B2O3 is 0% to 10%.

[0011] According to one aspect of the present disclosure, a method for preparing sealing glass is provided, the method comprising:

[0012] Dividing a sealing glass raw material into a first part and a second part, and mixing the first part and the second part respectively to form a first precursor raw material and a second precursor raw material, wherein the sealing glass raw material is any one of the sealing glass raw materials described above, and the first part at least includes SiO2, Al2O3 and BaO;

[0013] Heating the first precursor raw material to a first temperature and maintaining the temperature at the first temperature for a first time period;

[0014] Adding the second precursor raw material to the first precursor raw material after being kept warm for a first time, and stirring; heating the mixed raw material of the first precursor raw material and the second precursor raw material to a second temperature, and keeping the mixed raw material at the second temperature for a second time, so that the first precursor raw material and the second precursor raw material are melted and form a glass melt;

[0015] The glass melt is subjected to a preset treatment to form a sealing glass.

[0016] In an exemplary embodiment of the present disclosure, the second temperature is greater than the first temperature, and the second time period is greater than the first time period.

[0017] In an exemplary embodiment of the present disclosure, the glass melt is subjected to a preset treatment to form a sealing glass, comprising:

[0018] pouring the molten glass into deionized water to obtain glass slag;

[0019] Drying the glass slag at a third temperature, wherein the third temperature is lower than the first temperature;

[0020] Ball milling the dried glass slag to form glass powder;

[0021] The glass powder is processed by spray granulation to form glass spheres, and the glass spheres are pressed into glass blanks.

[0022] In an exemplary embodiment of the present disclosure, the first temperature is 400°C to 800°C, and the second temperature is 1300°C to 1650°C.

[0023] In an exemplary embodiment of the present disclosure, the first duration is 20 minutes to 60 minutes, and the second duration is 2 hours to 4 hours.

[0024] The sealing glass and preparation method thereof disclosed in the present invention, the silicon-oxygen bond (Si-O) in SiO2 has extremely high bond energy, which can form a stable three-dimensional network structure, thereby improving the softening temperature and chemical stability of the glass. The addition of Al2O3 can further enhance this network structure, because aluminum ions can replace silicon ions to form a more complex network structure, which can further improve the softening temperature and chemical stability of the glass. Na2O and K2O, as fluxing agents, can break silicon-oxygen bonds during the glass preparation process, making the glass network structure loose and more susceptible to thermal expansion, which helps to increase the thermal expansion coefficient of the glass, and can also reduce the melting point and viscosity of the glass. BaO has a larger ionic radius and a lower melting point, and is prone to forming larger gaps and defects in the glass, thereby helping to increase the thermal expansion coefficient of the glass.

[0025] The cobalt ions in Co3O4 can absorb light of a specific wavelength, making the glass appear in a specific color, which helps to improve the aesthetics and recognizability of the sealing parts and facilitates quick positioning. At the same time, the addition of Co3O4 can change the types and proportions of cations in the glass network, thereby enhancing the integrity and density of the network structure, which can directly affect the mechanical properties and chemical stability of the glass. Secondly, in terms of thermal properties, the addition of Co3O4 can adjust the proportion of metal oxides in the glass, so that sealing glass that matches the thermal expansion coefficient of the packaging material can be prepared, reducing deformation and cracking caused by thermal stress. In addition, an appropriate amount of Co3O4 can also optimize the melting and flow characteristics of the glass, reduce the softening point temperature, and facilitate the processing and application of the glass. Co3O4 also has a certain effect on the chemical stability of the glass, and can improve the corrosion resistance of the glass by forming new network structural units.

[0026] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0028] Figure 1 The present invention is a flow chart of a method for preparing sealing glass in an embodiment of the present invention. DETAILED DESCRIPTION

[0029] Example embodiments will now be described more fully with reference to the accompanying drawings. However, the example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present disclosure will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted. In addition, the drawings are only schematic illustrations of the present disclosure and are not necessarily drawn to scale.

[0030] Although relative terms such as "upper" and "lower" are used in this specification to describe the relative relationship of one component of the illustration to another component, these terms are used in this specification only for convenience, such as according to the orientation of the examples described in the drawings. It is understood that if the device of the illustration is turned upside down, the component described as "upper" will become the component "lower". When a structure is "on" other structures, it may mean that the structure is formed integrally on the other structure, or that the structure is "directly" disposed on the other structure, or that the structure is "indirectly" disposed on the other structure through another structure.

[0031] The terms "a", "an", "the", "said" and "at least one" are used to indicate the presence of one or more elements / components / etc.; the terms "including" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may exist in addition to the listed elements / components / etc.; the terms "first", "second" and "third" etc. are used merely as labels and are not intended to limit the quantity of their objects.

[0032] In the relevant technology, glass-sealed sealed connectors are indispensable connectors in various working environments such as high temperature, high pressure, and sealing, and are suitable for various special environments. Glass-sealed sealed connectors seal different electronic components through sealing glass, so that different materials or different components composed of the same material can be connected as a whole. As an inorganic adhesive, sealing glass can realize the interconnection between the same materials or different materials such as metal-metal, metal-ceramic, ceramic-ceramic, etc. It has good sealing and barrier properties, and is suitable for high reliability and high stability sealing requirements. At present, the thermal expansion properties, chemical stability, and softening temperature of sealing glass are not ideal, and it cannot be applied to a variety of materials to be sealed, and the sealing process is complicated.

[0033] Based on this, an embodiment of the present disclosure provides a sealing glass, which includes the following raw materials in molar percentage:

[0034] SiO2: 35% to 60%, Al2O3: 1% to 20%, Na2O: 2% to 20%, K2O: 2% to 20%, BaO: 0.5% to 25%, Co3O4: 0% to 15%.

[0035] In the sealing glass disclosed herein, the silicon-oxygen bond (Si-O) in SiO2 has extremely high bond energy and can form a stable three-dimensional network structure, thereby improving the softening temperature and chemical stability of the glass. The addition of Al2O3 can further enhance this network structure, because aluminum ions can replace silicon ions to form a more complex network structure, which can further improve the softening temperature and chemical stability of the glass. Na2O and K2O, as fluxing agents, can break silicon-oxygen bonds during the glass preparation process, making the glass network structure loose and more susceptible to thermal expansion, which helps to increase the thermal expansion coefficient of the glass, and can also reduce the melting point and viscosity of the glass. BaO has a larger ionic radius and a lower melting point, and is prone to forming larger gaps and defects in the glass, thereby helping to increase the thermal expansion coefficient of the glass.

[0036] The cobalt ions in Co3O4 can absorb light of a specific wavelength, making the glass appear in a specific color, which helps to improve the aesthetics and recognizability of the sealing parts and facilitates quick positioning. At the same time, the addition of Co3O4 can change the types and proportions of cations in the glass network, thereby enhancing the integrity and density of the network structure, which can directly affect the mechanical properties and chemical stability of the glass. Secondly, in terms of thermal properties, the addition of Co3O4 can adjust the proportion of metal oxides in the glass, so that sealing glass that matches the thermal expansion coefficient of the packaging material can be prepared, reducing deformation and cracking caused by thermal stress. In addition, an appropriate amount of Co3O4 can also optimize the melting and flow characteristics of the glass, reduce the softening point temperature, and facilitate the processing and application of the glass. Co3O4 also has a certain effect on the chemical stability of the glass, and can improve the corrosion resistance of the glass by forming new network structural units.

[0037] The following is a detailed description of the various parts and specific details of the sealing glass in the embodiment of the present disclosure:

[0038] In an exemplary embodiment of the present disclosure, the molar percentage of SiO2 may be 35% to 60%. For example, the molar percentage of SiO2 may be 35%, 38%, 45%, 50%, 55% or 60%, etc. The molar percentage of SiO2 may also be other values, which are not listed here one by one. From the molar percentage of SiO2, it can be seen that SiO2 is the main component of the sealing glass network structure. The high content of silicon-oxygen bonds can form a stable three-dimensional network, increase the viscosity of the glass liquid, reduce the tendency of the glass to crystallize, and help to increase the softening temperature of the sealing glass, thereby helping the sealing glass to maintain its shape and chemical stability in a high temperature environment, making it resistant to chemical erosion and oxidation.

[0039] The molar percentage of Al2O3 can be 1% to 20%. For example, the molar percentage of Al2O3 can be 1%, 5%, 10%, 15% or 20%, etc. The molar percentage of Al2O3 can also be other values, which are not listed here one by one. The addition of Al2O3 can further enhance this network structure, because aluminum ions can replace silicon ions to form a more complex network structure, which can further improve the softening temperature and chemical stability of the sealing glass. At the same time, Al2O3 can reduce the crystallization tendency and speed of the glass and improve the mechanical strength of the glass. Adding an appropriate amount of Al2O3 can improve the processability of the sealing glass, making the sealing glass easier to cut, polish and other processing operations. However, too high an Al2O3 content may cause the viscosity of the sealing glass to increase, affecting the fluidity and sealing performance of the sealing glass. Therefore, the molar percentage of Al2O3 in the present disclosure is a parameter range obtained after optimizing the ratio with other components, and this parameter range can balance the viscosity, softening temperature and chemical stability of the sealing glass.

[0040] The molar percentage of BaO can be 0.5% to 25%. For example, the molar percentage of BaO can be 0.5%, 5.5%, 7.5%, 8.5%, 15%, 20% or 25%, etc. The molar percentage of BaO can also be other values, which are not listed here one by one. BaO has a large ionic radius and a low melting point. Adding an appropriate amount of BaO to the components can form larger voids and defects in the sealing glass, thereby increasing the thermal expansion coefficient of the sealing glass, making it more compatible with the thermal expansion coefficient of the sealing material, thereby reducing problems such as cracking caused by thermal stress. However, too high a BaO content may cause the chemical stability of the glass to decrease. Therefore, the content of BaO needs to be optimized with other components. The molar percentage of 0.5% to 25% in the present disclosure can balance the chemical stability, viscosity and softening temperature of the sealing glass.

[0041] SiO2, Al2O3 and BaO in the present disclosure can form a SiO2-Al2O3-BaO system. Based on this system, the thermal expansion coefficient, glass softening temperature, chemical stability and other properties of the glass can be adjusted by adding various metal oxides.

[0042] In the present disclosure, the molar percentage of Na2O may be 2% to 20%, for example, the molar percentage of Na2O may be 2%, 6%, 10%, 14%, 18% or 20%, etc. The molar percentage of K2O may be 2% to 20%, for example, the molar percentage of K2O may be 2%, 6%, 10%, 14%, 18% or 20%, etc. The molar percentages of Na2O and K2O may also be other values, which are not listed here one by one. Na2O and K2O can be used as fluxes, which can break silicon-oxygen bonds during the glass preparation process, help reduce the viscosity of the glass, reduce the tendency of the glass to crystallize, make the glass network structure loose, more susceptible to thermal expansion, help increase the thermal expansion coefficient of the glass, and also reduce the melting point (improve fluidity) and viscosity of the glass. K2O can also improve the gloss of the glass, and within a specific molar percentage range, can improve the chemical stability of the glass. It should be noted that excessive Na2O content will greatly reduce the chemical stability, thermal stability and mechanical strength of glass, and easily cause glass to mold and increase the production cost of glass. Therefore, the present disclosure obtains the molar percentage of K2O (the percentage is 2% to 20%) and the molar percentage of Na2O (the percentage is 2% to 20%) that can increase the softening temperature of glass without affecting the stability of glass through precise calculation and countless experiments.

[0043] The molar percentage of Co3O4 can be 0% to 15%. For example, the molar percentage of Co3O4 can be 0, 0.5%, 2%, 4%, 10% or 15%. The cobalt ions in Co3O4 can absorb light of a specific wavelength, so that the glass presents a specific color. Therefore, Co3O4 is mainly used for coloring and improving the recognition of sealing glass, making the sealing glass more beautiful and highly recognizable. At the same time, the addition of Co3O4 can change the type and proportion of cations in the glass network, thereby enhancing the integrity and density of the network structure, and directly affecting the mechanical properties and chemical stability of the glass. Secondly, in terms of thermal properties, the addition of Co3O4 can adjust the proportion of metal oxides in the glass, so that sealing glass that matches the thermal expansion coefficient of the packaging material can be prepared, reducing deformation and cracking caused by thermal stress. In addition, an appropriate amount of Co3O4 can also optimize the melting and flow characteristics of the glass, reduce the softening point temperature, and facilitate the processing and application of the glass. Co3O4 also has a certain effect on the chemical stability of the glass, and can improve the corrosion resistance of the glass by forming new network structure units.

[0044] In an exemplary embodiment of the present disclosure, the raw materials of the sealing glass may further include MgO and / or ZnO, wherein the molar percentage of MgO may be 0% to 10%, for example, the molar percentage of MgO may be 0, 2%, 4%, 6%, 8% or 10%, etc. The molar percentage of ZnO may be 0% to 15%, for example, the molar percentage of ZnO may be 0, 5%, 10% or 15%. Of course, the molar percentages of MgO and ZnO may also be other values, which are not listed here one by one. MgO and ZnO can adjust the glass softening temperature of the glass, but excessive MgO and ZnO may cause a decrease in other properties of the glass. Therefore, the molar percentages of MgO and ZnO need to be strictly controlled.

[0045] In an exemplary embodiment of the present disclosure, the raw material of the sealing glass may further include one or more of CaO, P2O5 or ZrO2, wherein:

[0046] CaO can provide alkaline oxides for the SiO2-Al2O3-BaO system and adjust the acidity and alkalinity of the glass, thereby purifying the glass to a certain extent and improving its chemical stability; at the same time, CaO can also improve the wear resistance, compressive strength and hardness of the glass. In some embodiments of the present disclosure, the molar percentage of CaO can be 0% to 8%. For example, the molar percentage of CaO can be 0%, 2%, 4%, 6% or 8%. Of course, the molar percentage of CaO can also be other values, which are not listed here one by one. It should be noted that the molar percentage of CaO can be adaptively adjusted according to actual needs, and its molar percentage can be in the range of 0% to 8%.

[0047] Adding P2O5 to the SiO2-Al2O3-BaO system can introduce phosphorus into the silicate glass system. By introducing phosphorus, a small amount of phosphate glass can be formed in the sealing glass with silicate glass as the main body, so that the sealing glass can have the characteristics of both silicate glass and phosphate glass. A network structure of PO-Si bonds and POP bonds can be formed in the sealing glass, which helps to improve the chemical stability and thermal stability of the sealing glass and improve the strength of the sealing glass. The molar percentage of P2O5 can be 0% to 8%. For example, the molar percentage of P2O5 can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or 8%, etc. The molar percentage of P2O5 can be adaptively adjusted according to actual needs to meet the molar percentage range of 0% to 8%.

[0048] The addition of ZrO2 can form a perovskite structure, effectively reduce the diffusion of ions into the sealing glass, help increase the strength, hardness and wear resistance of the sealing glass, improve the fracture heat of the glass, and make the glass easier to handle and process. The molar percentage of ZrO2 is 0% to 6%. For example, the molar percentage of ZrO2 can be 0%, 1%, 2%, 3%, 4%, 5% or 6%. In some embodiments of the present disclosure, the molar percentage of ZrO2 can be adaptively adjusted according to actual needs, as long as its content is within the above range, and the present disclosure does not make specific limitations.

[0049] In an exemplary embodiment of the present disclosure, the raw materials of the sealing glass of the present disclosure may also include Rb2O. After Rb2O is added to the SiO2-Al2O3-BaO system, Rb2O, as an alkali metal oxide, has alkali metal ions (e.g., rubidium ions) with larger ionic radius and lower electronegativity, which can weaken the silicon-oxygen bonds in the glass network structure, making the glass easier to expand when heated, and helping to increase the thermal expansion coefficient of the glass. At the same time, because Rb2O has unique physical and chemical properties, such as a low melting point, it helps to lower the melting point of the material or the softening temperature of the glass. At the same time, Rb2O can be used as a catalyst. Adding Rb2O can accelerate or change the rate and path of the chemical reaction. At the same time, the rubidium ions (Rb2O) in Rb2O + ) will react with other ions in the material (such as Ba 2+ ) undergoes exchange or doping, thereby changing the crystal structure, electronic configuration or chemical properties of the material, affecting its physical and chemical properties. In some embodiments of the present disclosure, the molar percentage of Rb2O is 0% to 10%, for example, the molar percentage of Rb2O is 0%, 2%, 4%, 6%, 8% and 10%, etc.

[0050] In an exemplary embodiment of the present disclosure, the raw materials of the sealing glass of the present disclosure may also include Bi2O3 or B2O3, wherein the molar percentage of Bi2O3 may be 0% to 10%, for example, the molar percentage of Bi2O3 may be 0%, 2%, 4%, 6%, 8% or 10%, etc.; the molar percentage of B2O3 may be 0% to 10%, for example, the molar percentage of B2O3 may be 0%, 2%, 4%, 6%, 8% or 10%, etc. Of course, the molar percentages of Bi2O3 and / or B2O3 may also be other values, which are not listed here one by one.

[0051] Adding Bi2O3 to the SiO2-Al2O3-BaO system allows the Bi element to enter the network structure, which can improve the chemical stability of the sealing glass, expand the scope of use and environment of the sealing glass, and make it more suitable for special environmental requirements and sealing requirements of special devices.

[0052] As a flux, B2O3 can be added to the SiO2-Al2O3-BaO system to promote the liquid phase sintering process of the material, so that the material can achieve good densification at a lower temperature, thereby improving the mechanical properties and overall quality of the material. At the same time, the addition of B2O3 helps to inhibit the crystallization phenomenon in the material and maintain the amorphous state of the material by adjusting the glass network structure, which is crucial to maintaining the long-term stability and reliability of the material. In addition, B2O3 can also interact with other components to form new compounds or phases, thereby further optimizing the physical and chemical properties of the material.

[0053] It should be noted that the sealing glass provided by the present disclosure may include other substances not listed in addition to the above-mentioned substances. These substances may be conventional substances or elements for preparing glass, or these substances may be trace impurities or elements contained in the glass, but they will not have any effect or influence on the performance or use of the glass. These substances will not be described in detail here, but it should be understood that the present disclosure covers the conventional components and constituent materials of glass, and the above-mentioned substances do not limit other components of the sealing glass provided by the present disclosure.

[0054] In the embodiments provided in the present disclosure, the main components of the sealing glass (expressed in molar percentage) may include: SiO2: 35% to 60%, Al2O3: 1% to 20%, Na2O: 2% to 20%, K2O: 2% to 20%, BaO: 0.5% to 25%, Co3O4: 0% to 15%, MgO: 0% to 10%, ZnO: 0% to 15%, CaO: 0% to 8%, P2O5: 0% to 8%, ZrO2: 0% to 6%, Rb2O: 0% to 10%, Bi2O3: 0% to 10%, B2O3: 0% to 10%. The above 14 substances can be adjusted in molar percentage so that the total molar percentage is 100%, constituting the sealing glass raw material. By adjusting the molar percentage of the above substances, the thermal expansion coefficient of the sealing glass can be made to be α=86.2×10 -7 ~163×10 -7 / ℃, the softening temperature of sealing glass Ts=630~766.2℃.

[0055] Among them, the determination of the thermal expansion coefficient of the sealing glass is obtained at 20 to 300°C in accordance with the national standard (GB / T7962.16-2010) or the commonly used technical means in the field. If it is necessary to obtain the thermal expansion coefficient at other temperatures, the temperature can be changed, and the thermal expansion coefficient at different temperatures can be obtained by the commonly used technical means or instruments in the field (such as thermal expansion meter or thermogravimetric analyzer). The softening temperature of the sealing glass can be determined in accordance with the national standard (SJ690-83) or the commonly used technical means in the field. For example, the softening temperature can be obtained by using the resistance method, differential thermal analysis method or viscosity method.

[0056] By adjusting the thermal expansion coefficient and softening temperature of the sealing glass, the sealing glass can be made suitable for sealing a variety of materials to be sealed, thereby expanding the application range of the sealing glass. For example, it can be used for sealing a variety of materials such as metal and metal, ceramic and metal.

[0057] The density of the sealing glass provided by the present disclosure can be 3.70-3.91 g / cm 3 Glass with different densities can be used in different electronic components or different parts of the same electronic component.

[0058] The sealing temperature of the sealing glass provided in the present disclosure needs to be greater than the softening temperature of the sealing glass, so that the sealing glass can be softened to melt during sealing. After the film of the material to be sealed forms a sealing glass film, the sealing glass is solidified to interconnect the materials to be sealed. In the present disclosure, the reference sealing system of the sealing glass can be 900°C to 1240°C, and the sealing temperature must be at least greater than 900°C, that is, the sealing temperature can be greater than or equal to 900°C. At the sealing temperature, the sealing glass needs to be insulated so that the sealing glass can fully undergo a state transition. Normally, the insulation time can be 30 to 50 minutes, and the specific insulation time can be adaptively adjusted according to the different sealing temperatures. The determination of the sealing temperature of the sealing glass can be obtained by adopting the national standard (SJ / T3231-2005) or the commonly used technical means in the field, but is not limited thereto.

[0059] In the embodiments provided in the present disclosure, the components of the sealing glass can be prepared by the salts or acid-base compounds corresponding to the oxides. For example, CaO is not easily available in the natural environment and is relatively expensive. CaO can be prepared by CaCO3, which is relatively cheap and easily available. CaCO3 can be directly decomposed under high temperature conditions to obtain CaO and CO2, wherein CO2 is discharged in the form of gas and does not affect the preparation process of the glass. For other metal oxides, they can be obtained by a preparation method similar to that of CaO, but it should be noted that the components of the sealing glass are the above-mentioned metal oxides and do not include other substances such as various salts or acid-base compounds for preparing the above-mentioned metal oxides. Preferably, the corresponding metal oxides are prepared by metal salts or their acid-base compounds, and usually the by-products thereof can be stable gases or water. While the by-products are easy to discharge, they will not have an adverse effect on the process of sealing the glass.

[0060] The present disclosure also provides a method for preparing sealing glass. Figure 1 A flow chart of the method for preparing the sealing glass disclosed in the present invention is shown, as Figure 1 As shown, the preparation method may include steps S110 to S140, wherein:

[0061] Step S110, dividing the sealing glass raw material into a first part and a second part, and mixing the first part and the second part respectively to form a first precursor raw material and a second precursor raw material, the sealing glass raw material is any of the sealing glass raw materials mentioned above, and the first part at least includes SiO2, Al2O3 and BaO;

[0062] Step S120, heating the first precursor raw material to a first temperature, and keeping the temperature at the first temperature for a first time period;

[0063] Step S130, adding the second precursor raw material to the first precursor raw material after being kept warm for a first time, and stirring; heating the mixed raw material of the first precursor raw material and the second precursor raw material to a second temperature, and keeping it warm at the second temperature for a second time, so that the first precursor raw material and the second precursor raw material are melted and a glass melt is formed;

[0064] Step S140 , performing a preset process on the molten glass to form a sealing glass.

[0065] The sealing glass preparation method disclosed in the present invention scientifically divides the sealing glass raw materials into two parts and mixes them separately to form a first precursor raw material and a second precursor raw material, thereby ensuring the precise proportion and uniform mixing of the raw materials. By precisely controlling the heating temperature and the heat preservation time, the first precursor raw material is fully reacted and fused, and then the second precursor raw material is added and stirred, and the temperature is further raised to an appropriate temperature so that the two are completely melted and a glass melt is formed. In this process, strict control of temperature and time avoids thermal stress and component segregation caused by rapid temperature rise, and ensures the uniformity and stability of the glass melt. Finally, the glass melt is pre-treated to form high-quality sealing glass. This preparation method not only improves the product quality and performance of the sealing glass, such as transparency, sealing performance, chemical stability and mechanical strength, but also provides a more reliable and efficient solution for the production and application of sealing glass, meeting the needs of various sealing applications.

[0066] The following is a detailed description of the various steps and specific details of the method for preparing the encapsulated glass provided in the embodiment of the present disclosure:

[0067] like Figure 1 As shown, in step S110, the sealing glass raw material is divided into a first part and a second part, and the first part and the second part are mixed respectively to form a first precursor raw material and a second precursor raw material, the sealing glass raw material is the raw material of any of the above-mentioned sealing glasses, and the first part includes at least SiO2, Al2O3 and BaO.

[0068] The raw materials of the sealing glass may include SiO2 powder, Al2O3 powder, BaO powder, and one or more of MgO powder, ZnO powder, CaO powder, P2O5 powder, ZrO2 powder, Rb2O powder, Bi2O3 powder, and B2O3 powder. The raw materials of the sealing glass including the above components may be divided into two parts and mixed evenly to form a first precursor raw material and a second precursor raw material. For example, the raw materials of the sealing glass may be divided into a first part and a second part, and the types of raw materials in the first part and the second part are different, wherein the first part includes raw materials with a relatively high melting point, for example, the first part may include at least SiO2 powder, Al2O3 powder and BaO powder, and the rest may be used as the second part. Of course, the above is only illustrative, and the division of the mixed raw materials may be selected according to factors such as actual heating requirements or heating equipment, and the present disclosure does not make specific limitations.

[0069] The first part and the second part can be weighed according to the formula and placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed to obtain the first precursor raw material and the second precursor raw material that are evenly dispersed.

[0070] Step S120, heating the first precursor raw material to a first temperature, and maintaining the temperature at the first temperature for a first period of time.

[0071] The first temperature may be 400°C to 800°C, for example, it may be 400°C, 500°C, 600°C, 700°C or 800°C. Of course, the first temperature may also be other values, which are not listed here one by one. The first duration may be 20min to 60min, for example, the first duration may be 20min, 30min, 40min, 50min or 60min. Of course, the first duration may also be other values, which are not listed here one by one. The prepared first precursor raw material may be placed in a crucible, and then placed in a Maffei furnace, and the temperature may be increased from 25°C to the first temperature at a heating rate of 5°C / min to 12°C / min, and the temperature may be kept at the first temperature for the first time to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of part of the raw material.

[0072] Step S130, adding the second precursor raw material to the first precursor raw material after being kept warm for a first period of time, and stirring; heating the mixed raw material of the first precursor raw material and the second precursor raw material to a second temperature, and keeping it warm at the second temperature for a second period of time, so that the first precursor raw material and the second precursor raw material are melted to form a glass melt.

[0073] In the present disclosure, in order to ensure that all raw materials can be melted, the second temperature can be greater than the first temperature. For example, the second temperature can be 1300°C to 1650°C. For example, the second temperature can be 1300°C, 1400°C, 1500°C, 1600°C or 1650°C. Of course, the second temperature can also be other values, which are not listed here one by one. At the same time, in order to ensure that all raw materials can be completely melted, the second duration can be greater than the first duration. For example, the second duration can be 2 hours to 4 hours. For example, the second duration can be 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours. Of course, the second duration can also be other values, which are not listed here one by one.

[0074] After the first precursor is kept warm for the first time, the Maffei furnace can be opened, and the mixed second precursor raw material can be added to the first precursor raw material that has been kept warm. After stirring, the temperature can be raised to the second temperature at a rate of 8°C / min to 15°C / min, and kept warm at the second temperature for the second time. At the end of the insulation, the first precursor raw material and the second precursor raw material have melted to form a glass melt. During the insulation process, it can be stirred several times to better disperse and mix the raw materials. Because the raw materials contain Co3O4, under the action of Co ions, the glass melt finally formed presents a unique blue color, and the depth of the blue color depends on the molar percentage of Co3O4.

[0075] Step S140 , performing a preset process on the molten glass to form a sealing glass.

[0076] The glass melt may be subjected to a preset treatment to obtain the sealing glass of the present disclosure. For example, the glass melt may be subjected to a preset treatment to form the sealing glass (i.e., step S140) may include steps S210 to S240, wherein:

[0077] Step S210, pouring the molten glass into deionized water to obtain glass slag.

[0078] The high-temperature molten glass can be cooled by deionized water to obtain glass slag. For example, the high-temperature molten glass can be quickly poured into deionized water to obtain dark blue glass slag by rapid water quenching.

[0079] Step S220, drying the glass slag at a third temperature, where the third temperature is lower than the first temperature.

[0080] In order to avoid melting the glass slag during the drying process, the third temperature can be lower than the first temperature. For example, the third temperature can be 90°C to 150°C, for example, the third temperature can be 90°C, 110°C, 130°C or 150°C. Of course, the third temperature can also be other temperatures, which are not listed here. For example, all the blue glass slag can be collected and placed in a drying oven, and dried at the third temperature for 24 hours to fully dry the glass slag.

[0081] Step S230, ball-milling the dried glass slag to form glass powder.

[0082] The dried glass slag can be placed in a grinding device (such as a corundum ball mill) and ground at a speed of 300 r / min to 650 r / min for 5 hours to obtain glass powder, and the ground glass powder can be sieved, for example, 100 mesh sieve to obtain a blue sealing glass material.

[0083] Step S240: Process the glass powder by spray granulation to form glass spheres, and press the glass spheres into glass blanks.

[0084] For example, glass powder can be sprayed into a granulation tower, and the glass powder is agglomerated under the action of the spray hot air, thereby obtaining spherical granules. The glass spheres formed by this method have good precision and uniform particles. Of course, other methods can also be used to process the glass powder to obtain glass spheres, which are not specifically limited here. The glass spheres can be pressed into glass blanks for subsequent packaging.

[0085] It should be noted that, although the steps of the method for preparing encapsulated glass in the present disclosure are described in a specific order in the accompanying drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.

[0086] The technical solution of the present disclosure will be described below with reference to specific embodiments:

[0087] Example 1

[0088] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 35%, Al2O3: 12%, Na2O: 14%, K2O: 18%, BaO: 8.5%, Co3O4: 2%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5%, Bi2O3: 1%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 35%, Al2O3: 12%, Na2O: 14%, K2O: 18% and BaO: 8.5%; the second part includes Co3O4: 2%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5% and Bi2O3: 1%.

[0089] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0090] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0091] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0092] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0093] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0094] Example 2

[0095] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 38%, Al2O3: 11%, Na2O: 16%, K2O: 12%, BaO: 7.5%, Co3O4: 4%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5%, Bi2O3: 2%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 38%, Al2O3: 11%, Na2O: 16%, K2O: 12% and BaO: 7.5%; the second part includes Co3O4: 4%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5% and Bi2O3: 2%.

[0096] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0097] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0098] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0099] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0100] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0101] Example 3

[0102] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 35%, Al2O3: 12%, Na2O: 14%, K2O: 20%, BaO: 8.5%, Co3O4: 0.8%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5%, ZrO2: 0.2%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 35%, Al2O3: 12%, Na2O: 14%, K2O: 20% and BaO: 8.5%; the second part includes Co3O4: 0.8%, ZnO: 7.5%, CaO: 1.5%, MgO: 0.5% and ZrO2: 0.2%.

[0103] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0104] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 800°C at a heating rate of 12°C / min, and keeping it at 800°C for 60 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1650°C at a heating rate of 15°C / min, and keeping it at 1650°C for 4 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0105] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0106] 5) Collect all the blue glass debris and put them in a drying oven, set the drying oven temperature at 150°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 650 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0107] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0108] Example 4

[0109] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 45%, Al2O3: 12%, Na2O: 8%, K2O: 17%, BaO: 7.5%, Co3O4: 2%, ZnO: 7.5%, CaO: 0.5%, MgO: 0.3%, ZrO2: 0.2%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 45%, Al2O3: 12%, Na2O: 8%, K2O: 17% and BaO: 7.5%; the second part includes Co3O4: 2%, ZnO: 7.5%, CaO: 0.5%, MgO: 0.3%, ZrO2: 0.2%.

[0110] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0111] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0112] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0113] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0114] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0115] Example 5

[0116] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 60%, Al2O3: 12%, Na2O: 12%, K2O: 5%, BaO: 5.5%, Co3O4: 2%, Bi2O3: 1%, CaO: 0.5%, MgO: 1.5%, ZrO2: 0.5%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 60%, Al2O3: 12%, Na2O: 12%, K2O: 5% and BaO: 5.5%; the second part includes Co3O4: 2%, Bi2O3: 1%, CaO: 0.5%, MgO: 1.5% and ZrO2: 0.5%.

[0117] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0118] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0119] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0120] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0121] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0122] Example 6

[0123] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 35%, Al2O3: 1%, Na2O: 2%, K2O: 2%, BaO: 0.5%, Co3O4: 0.5%, ZnO: 15%, ZrO2: 6%, P2O5: 8%, Bi2O3: 10%, Rb2O%: 10%, B2O3: 10%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 35%, Al2O3: 1%, Na2O: 2%, K2O: 2% and BaO: 0.5%; the second part includes Co3O4: 0.5%, ZnO: 15%, ZrO2: 6%, P2O5: 8%, Bi2O3: 10%, Rb2O%: 10% and B2O3: 10%.

[0124] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0125] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0126] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0127] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0128] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0129] Example 7

[0130] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 35%, Al2O3: 20%, Na2O: 2%, K2O: 2%, BaO: 25%, P2O5: 8%, CaO: 8%. The above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 35%, Al2O3: 20%, Na2O: 2%, K2O: 2% and BaO: 25%; the second part includes P2O5: 8% and CaO: 8%.

[0131] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0132] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0133] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0134] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0135] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0136] Example 8

[0137] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 35%, Al2O3: 1%, Na2O: 20%, K2O: 18.5%, BaO: 0.5%, Co3O4: 15%, MgO: 10%. The above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 35%, Al2O3: 1%, Na2O: 20%, K2O: 18.5% and BaO: 0.5%; the second part includes Co3O4: 15%, MgO: 10%.

[0138] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0139] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0140] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0141] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0142] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0143] Example 9

[0144] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 42%, Al2O3: 10.5%, Na2O: 14.5%, K2O: 16%, BaO: 7.5%, Co3O4: 9.5%. The above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into a first part and a second part, wherein the first part includes: SiO2: 42%, Al2O3: 10.5%, Na2O: 14.5%, K2O: 16%, BaO: 7.5%; the second part includes Co3O4: 9.5%.

[0145] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0146] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0147] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0148] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0149] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0150] Example 10

[0151] 1) The sealing glass is composed of the following raw materials in molar percentage: SiO2: 60%, Al2O3: 3%, Na2O: 5%, K2O: 2.5%, BaO: 4%, Co3O4: 9.4%, MgO: 8%, ZnO: 6%, Bi2O3: 0.6%, Rb2O: 1%, B2O3: 0.5%. Among them, the above-mentioned oxides should include their salts and acid-base compounds. The above-mentioned raw materials are divided into the first part and the second part, wherein the first part includes: SiO2: 60%, Al2O3: 3%, Na2O: 5%, K2O: 2.5%, BaO: 4%; the second part includes Co3O4: 9.4%, MgO: 8%, ZnO: 6%, Bi2O3: 0.6%, Rb2O: 1%, B2O3: 0.5%.

[0152] 2) After weighing the raw materials of the first part and the second part according to the formula, they are placed in a high-speed mixer for mixing and dispersion, so that the different raw materials are fully mixed, thereby obtaining a uniformly dispersed first precursor raw material and a second precursor raw material.

[0153] 3) placing the first precursor raw material in a customized crucible, and then placing it in a muffle furnace, heating the temperature from 25°C to 400°C at a heating rate of 5°C / min, and keeping it at 400°C for 20 minutes to promote the evaporation of moisture in the hygroscopic raw material and the decomposition of some raw materials; opening the muffle furnace and adding the second precursor raw material, stirring it, and then heating it to 1300°C at a heating rate of 8°C / min, and keeping it at 1300°C for 2 hours; during this period, stirring is performed multiple times to better disperse and mix the first precursor raw material and the second precursor raw material, and finally a completely melted blue glass melt is obtained.

[0154] 4) The high-temperature blue glass melt is quickly poured into the prepared deionized water, and dark blue glass slag is obtained by rapid water quenching.

[0155] 5) Collect all the blue glass debris and put them in a drying oven, set the temperature of the drying oven to 90°C, dry them for 24 hours, put the dried glass debris in a corundum ball mill, grind them at a speed of 300 r / min for 5 hours, and pass them through a 100-mesh sieve to obtain blue glass powder.

[0156] 6) The ball-milled glass powder is treated by a spray granulation method to obtain a glass sphere, which is then pressed into a glass blank for subsequent sealing.

[0157] The thermal expansion coefficient, softening temperature and density of the sealing glass prepared in each embodiment of the present invention are tested respectively, as follows:

[0158]

[0159]

[0160] It should be noted that in the present disclosure, the thermal expansion coefficient of the sealing glass is mainly affected by the molar percentage of Na2O and K2O, and the influence of other components on the thermal expansion coefficient of the sealing glass is not obvious. At the same time, the softening temperature of the glass is mainly affected by the molar percentage of Si2O, and the influence of other components on the softening temperature of the sealing glass is not obvious.

[0161] By comparing Examples 1 to 3 and Examples 6 to 8, it can be seen that under the synergistic effect of Co3O4, the greater the molar percentage of Na2O and K2O, the greater the thermal expansion coefficient. This is because: in the structure of glass, silicon atoms and oxygen atoms are tightly bound by covalent bonds to form a continuous three-dimensional network structure, and the alkali metal ions (sodium ions and potassium ions) in Na2O and K2O have a strong electric field effect, which can attract and weaken the oxygen atoms in the silicon-oxygen bond, resulting in partial rupture of the silicon-oxygen network. This process not only lowers the melting point of the glass, but also makes the originally tight network structure relatively loose, more susceptible to thermal expansion, and helps to increase the thermal expansion coefficient of the glass.

[0162] By comparing Example 2, Example 4, Example 5, Example 9 and Example 10, it can be seen that as the SiO2 mole percentage increases, the glass softening temperature increases gradually. This is because as the SiO2 (silicon dioxide) mole percentage increases in the glass, the number of silicon oxygen bonds (Si-O-Si) in the glass network structure increases accordingly. These silicon oxygen bonds have a high degree of stability and a strong bonding force, making the overall structure of the glass more compact and firm. Therefore, to destroy this more stable structure to achieve a softened state, a higher temperature is required. Therefore, as the SiO2 mole percentage increases, the softening temperature of the glass will gradually increase.

[0163] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure, which follow the general principles of the present disclosure and include common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The description and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A sealing glass, characterized in that: The sealing glass comprises the following raw materials in molar percentage: SiO2: 35% to 60%, Al2O3: 1% to 20%, Na2O: 2% to 20%, K2O: 2% to 20%, BaO: 0.5% to 25%, Co3O4: 0% to 15%.

2. The sealing glass according to claim 1, characterized in that: The raw materials of the sealing glass further include one or more of MgO and / or ZnO, wherein the molar percentage of the MgO is 0% to 10%, and the molar percentage of the ZnO is 0% to 15%.

3. The sealing glass according to claim 1, characterized in that: The raw materials of the sealing glass also include one or more of CaO, P2O5 or ZrO2, wherein the molar percentage of CaO is 0% to 8%, the molar percentage of P2O5 is 0% to 8%, and the molar percentage of ZrO2 is 0% to 6%.

4. The sealing glass according to claim 1, characterized in that: The sealing glass further comprises Rb2O, and the molar percentage of Rb2O is 0% to 10%.

5. The sealing glass according to claim 1, characterized in that: The raw materials of the sealing glass further include Bi2O3 or B2O3, wherein the molar percentage of the Bi2O3 is 0% to 10%, and the molar percentage of the B2O3 is 0% to 10%.

6. A method for preparing sealing glass, characterized in that: The preparation method comprises: Dividing a sealing glass raw material into a first part and a second part, and mixing the first part and the second part respectively to form a first precursor raw material and a second precursor raw material, wherein the sealing glass raw material is the raw material of the sealing glass according to any one of claims 1 to 5, and the first part at least comprises SiO2, Al2O3 and BaO; Heating the first precursor raw material to a first temperature and maintaining the temperature at the first temperature for a first time period; Adding the second precursor raw material to the first precursor raw material after being kept warm for a first time, and stirring; heating the mixed raw material of the first precursor raw material and the second precursor raw material to a second temperature, and keeping the mixed raw material at the second temperature for a second time, so that the first precursor raw material and the second precursor raw material are melted and form a glass melt; The glass melt is subjected to a preset treatment to form a sealing glass.

7. The preparation method according to claim 6, characterized in that: The second temperature is greater than the first temperature, and the second time period is greater than the first time period.

8. The preparation method according to claim 7, characterized in that: The glass melt is subjected to a preset treatment to form a sealing glass, comprising: pouring the molten glass into deionized water to obtain glass slag; Drying the glass slag at a third temperature, wherein the third temperature is lower than the first temperature; Ball milling the dried glass slag to form glass powder; The glass powder is processed by spray granulation to form glass spheres, and the glass spheres are pressed into glass blanks.

9. The preparation method according to claim 7, characterized in that: The first temperature is 400°C to 800°C, and the second temperature is 1300°C to 1650°C.

10. The preparation method according to claim 7, characterized in that: The first duration is 20 minutes to 60 minutes, and the second duration is 2 hours to 4 hours.

Citation Information

Patent Citations

  • Sealing material for photo-thermal absorbing glass and preparation method of sealing material

    CN107399908A

  • Sealing glass, preparation method thereof and electronic component

    CN117735841A

  • Slag composite for sealing device of flat display panel and sealing device fabricated using the same

    KR1020100129644A

  • Sealant composition for tempered glass panel

    KR1020170011866A

  • Seal structure of ceramics and low expansion metallic material

    US4135038A